Understanding the dynamics and identify entry points to build resilience in groundnut value chain in Senegal: A group model building approach - Kumar, Shalander; Das, Abhishek; Yessoufou, Adjani Nourou-dine; Beye, Assane; Gueye, Fama; Worou, Omonlola Nadine; Whitbread, Anthony (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This working paper focuses on analyzing the dynamics of the peanut value chain in Senegal and identifying entry points to enhance its resilience. Using an innovative Group Model Building approach, the study explores the complexities of the chain, which is central to Senegalese agriculture, covering 40% of the total cultivated area. The groundnut value chain, largely in the hands of smallholders, is a crucial income source for the rural population. However, it faces challenges such as climate pressures, aging infrastructure, and unregulated trader entry, exacerbating vulnerability despite stakeholder efforts. Supply complexities include factors like production systems, climatic conditions, and access to essential inputs. Seeds and fertilizers are critical, but farmers struggle with insufficient quantities, ineffective governance, and limited access to mechanization. This results in low productivity, unstable yields, and high production costs. Climate risks, compounded by low access to climate information services (CIS) and climate- smart agricultural practices (CSAP) training, further impact yields and increase vulnerability. Land degradation adds another dimension to climate risk, affecting both yield and land use for peanut production. The study recommends an innovative Group Model Building approach to gain insights into the groundnut value chain dynamics through causal loop diagrams. The objective is to formulate policy recommendations to strengthen the sustainability and resilience of the peanut value chain, addressing challenges related to inputs, climate risks, and training.